Intention for Hepatitis B Vaccination among Male-to-female Transgenders in Bandung - Ain Izzati Khiruddin; Irvan Afriandi; Laili Aznur; Elsa Pudji Setiawati (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Hepatitis B is still an alarming global disease nowadays. The majority of transmission is by sexual activity during adulthood and male-to-female transgender is a high risk group. Despite protective vaccine is available, vaccination coverage among these high risk groups remained low. This study aimed to compare the differences in attitude, subjective norms, and perceived behavioral control between the intended group and unintended group for hepatitis B vaccination among male-to-female transgenders in Bandung.Methods: A Cross-sectional study was conducted during September–November 2012 to 100 male-to-female transgenders residing in Bandung. Thirteen Likert scales validated questionnaires were used to compare the attitude, subjective norms and perceived behavioral control by their intention of hepatitis B vaccination (Theory of Plan Behavior/TPB). the respondents were recruited by the help of Srikandi Pasundan, that actively works in the issues of transgender. The inclusion criterias were they regard themselves as waria, consistent as a transgender for at least six months, residing in Bandung, and sexually active within six months. Independent variables consist of demographic characteristics and TPB construct variables. Mann Whitney Test was used to analyze the data.Results: Among 75% of the unvaccinated respondents, majority (70.7%) have the intention to get hepatitis B vaccination. Mann Whitney analysis showed that there is a difference of attitude between the intended group and unintended group for hepatitis B vaccination, while there are no differences by their intention for subjective norms and perceived behavioral control.Conclusion: The attitude influenced vaccination intention among male-to-female transgenders in Bandung. [AMJ.2015;2(1):253–61]